Orthodontic treatment on non vital tooth - Eka Erwansyah; Nurhayaty Natsir; Andi Winda Puspitasari (Makassar Dental Journal, 2020)
Background: Orthodontic treatment is closely related to the physiological changes of the pulp and periodontal tissues, with no exception to the non-vital tooth. That tooth is having significant physiological changes due to the absence of vascularisation problems, which would affect the solitary structures around the tooth. Orthodontic treatment in non vital tooth is such a challange to the dentists in determining treatment planning, it was all caused by physiology and pathology changing that might appear during or even after the orthodontic treatment. Objective: Explains about orthodontic treatment in a non vital tooth after having an endodontic treatment. Conclusion: Orthodontic treatment in a non-vital tooth showed a good prognosis because of the absence of cementoblast which is inducted by pulp vascularisation. Beside that, there are some risks that might appear after the tooth being treated by orthodontic treatment, those are pseudooverfilling, reactivation of the previous lesion, the incrase of partial/total regression, the increase of endodontic lesion, apical root resorption, ankylosis, or even dental fracture.